A comparative study of the virulence factors of Klebsiella spp. Isolated from different environments - Naguib, Laith Mosleh; Hamdy, Nagham Mued (Arab Journal for Sciences and Research Publishing, 2016)
The Current study conducted to investigate of different virulence factors for bacterial isolates resistant to antibiotics and isolated from different environments. where it was collected 247 clinical and environmental samples from different sources isolated on Nutrient agar media.    The results of bacterial culture have shown that 46 isolation dating back to the bacterium Klebsiella spp , isolates  also showed mixed results towards  antibiotics . and antibiotic sensitivity results were selected 18 bacterial isolates resistant to antibiotics to study some of the virulence factors ant to investigate the genes responsible for the kinship between the isolates using (PCR), and the results showed the overall rate of similarity of isolates sick and environmental by 64%, which shows that source of bacterial infections maybe caused by contact with water or soil.
Keywords: Klebsiellapneumonia; antibiotic resistance; Klebsiella virulence factors